Metamorphic Complex Deformation in North Bangka Island Based on Macrostructures and Microstructures Evidences - Hendrawan, Rezki; Draniswari, Windi Anarta; Wahyuni, Fitri Indah; Sapiie, Benjamin; Basuki, Nurcahyo Indro (UIR PRESS, 2024)
The northern Bangka Island is composed of Pemali metamorphic complex which is indicated by the collision between Indochina and Sibumasu blocks. These features are interesting to observe because the metamorphic rocks could be recorded in some geological structures at different times. The study began by conducting field observation on Pemali Metamorphic Complex as objects. Field observation aims to collect lithological data, structural data, and oriented rock samples. The results of field pitching were processed to determine macrostructures, microstructures, and mineral distribution. The data was analyzed based on kinematic, descriptive, and deformation mechanisms to determine the deformation patterns that occurred in the study area. Field and oriented thin section data show structures and occurred in different deformation conditions. The analysis based on macrostructures and microstructures showed that the northern part of Bangka Island experienced three different deformation phases. Deformation begins with the formation of folds that are associated with collisions between Sibumasu-Indochina, followed by a second deformation that forms a fold with different verging. Both deformations are formed in the ductile zone and the brittle-ductile transition zone. The third deformation occurs when rocks have been lifted to the surface by the presence of faults, joints, and veins. The sequence of the deformation model is similar to the deformation experienced in the Bentong-Raub suture zone formed in the shear zone.